Инновации как угроза: неожиданное «прочтение» Шумпетера - Avdeenko, Galina; Dmitriev, Sergey (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2018)
The article contains an analysis of the consequences of unequitable development and economic growth in different countries; the authors assumes that the reason of this phenomenon is the difference in innovation activity of the economic agents which results in unequal growth; according to authors this is the result of ‘creative destruction’ principle of Joseph Schumpeter.